Preservice Teachers Reflections on Risk-Taking: The Dynamics of Practice and Experience While Experimenting With Innovation During Student Teaching - Gwyn-Paquette, Caroline; Tochon, François Victor (Alberta Journal of Educational Research, 2003)
In this study we explore the reflections of 14 preservice teachers preparing for English as a second language (ESL) or social science teaching in high school. We wished to know what encouraged them to experiment with innovative practice, notably cooperative learning, during their practicum: what they perceived as tolerable and intolerable risk factors, and what helped them to persist in trying the new approach. Inductive analysis of the transcripts of recorded planning and post-observation conversations with the participants reveals that once the impetus for the process is provided, risk-taking in student teaching depends primarily on students' reactions in the classroom, an effective support system for planning, and feedback from either the supervisor and/or the cooperating teacher, as well as from peers, in an atmosphere of mutual trust.